Penyuluhan Penurunan Kasus Stunting untuk Meningkatkan Kualitas Generasi Muda di Desa Hambalang - N Nurhadiyanta; Miftahul Huda Fendiyanto; Hayatul Khairul Rahmat; Daivy Atiya Advisa; Mutia Meireni (Yayasan REDI Tiga Monas, 2023)
This community service activity aims to provide knowledge and insight regarding improving the quality of the younger generation to reduce cases of stunting in Hambalang Village, Citeureup District, Bogor Regency. The stages in implementing community service activities start from the preparation stage, implementation stage, and evaluation stage. The method used in this community service activity is the lecture and question and answer method. Through this activity, it is hoped that the people of Hambalang Village, Citeureup District, Bogor Regency will have insight into improving the quality of the young generation to reduce stunting cases in Hambalang Village, Citeureup District, Bogor Regency.